The individual contribution and relative importance of self-management and quality of care on glycaemic control in type 2 diabetes - Yolanda V. Martínez; Stephen M. Campbell; Mark Hann; Peter Bower (Instituto Nacional de Salud Pública, 2016)
Objective. To evaluate the relative importance of self-management (SM) and quality of care (QoC) inpredicting glycaemic control in patients with type 2 diabetes. Materials and methods. A longitudinal cohort study was conducted in 204 adults diagnosed with type 2 diabetes. Self-management and quality of care were measured at baseline. HbA1c was measured at baseline and at six-month follow-up. Results. None of the measures of self-management were significantly associated with HbA1c. Treatment intensification (TI) (a proxy for quality of care) resulted in lower HbA1c at follow-up. Other variables were associated with HbA1c at follow-up: HbA1c at baseline, age, diabetes duration, and combination of oral glucose-lowering medications. An exploratory analysis showed that patients who did not receive treatment intensification but performed more self-management behaviours had lower HbA1c levels at follow-up. Conclusion. Treatment intensification might be more important for glycaemic control than self-management but the interaction between treatment intensification and self-management needs further research.   DOI: http://dx.doi.org/10.21149/spm.v58i4.8020